Efficiency Enhancement of PbS Quantum Dot/ZnO Nanowire Bulk-Heterojunction Solar Cells by Plasmonic Silver Nanocubes - Kawawaki, Tokuhisa; Wang, Haibin; Kubo, Takaya; Saito, Koichiro; Nakazaki, Jotaro; Segawa, Hiroshi; Tatsuma, Tetsu (ACS nano, 2015)
For improvement of solar cell performance, it is important to make efficient use of near-infrared light, which accounts for ∼40% of sunlight energy. Here we introduce plasmonic Ag nanocubes (NCs) to colloidal PbS quantum dot/ZnO nanowire (PbS QD/ZnO NW) bulk-heterojunction solar cells, which are characterized by high photocurrents, for further improvement in the photocurrent and power conversion efficiency (PCE) in the visible and near-infrared regions. The Ag NCs exhibit strong far field scattering and intense optical near field in the wavelength region where light absorption of PbS QDs is relatively weak. Photocurrents of the solar cells are enhanced by the Ag NCs particularly in the range 700–1200 nm because of plasmonic enhancement of light absorption and possible facilitation of exciton dissociation. As a result of the optimization of the position and amount of Ag NCs, the PCE of PbS QD/ZnO NW bulk-heterojunction solar cells is improved from 4.45% to 6.03% by 1.36 times.